Modeling Fiscal Sustainability in Dynamic Macro-Panels with Heterogeneous Effects: Evidence from German Federal States - Lars P. Feld; Ekkehard A. Köhler; Julia Wolfinger (Center for Economic Studies and ifo Institute (CESifo), 2018)
In this paper, we extend Henning Bohn's (2008) fiscal sustainability test by allowing for slope heterogeneity and cross-sectional dependence (CD). In particular, our econometric approach is the first that allows fiscal reaction functions (FRF) to capture unobserved heterogeneous effects from business and fiscal policy cycles. We apply this econometric approach to sub-national public finance data of the German Laender between 1950 and 2015 and find that their fiscal policy only partly meets fiscal sustainability criteria. According to our results, politicians have significantly reacted to increasing debt levels by increasing budget surpluses since 1991. However, time-series evidence for longer periods does not indicate a significant and positive reaction to increasing debt levels in the West German Laender panel.
Keywords: H62; H77; H72; C23; 330; fiscal sustainability; public debt; panel data; cross-sectional dependence